BIOTECHNOLOGICAL PROCESSING OF ORGANIC POULTRY WASTE AND ITS USE IN AGRICULTURE - Saimnazarov Yuldash Bekmirzaevich, (EPRA International Journal of Research and Development (IJRD), 2022)
Up-to-date biotechnologies are involved in the biological transformation of organic poultry waste into an environmentally friendly fertilizer that can preserve soil fertility and significantly improve yields. Currently, no more than 35% of livestock manure is used as a fertilizer in Uzbekistan. The use of poultry manure at poultry farms in Uzbekistan has been poorly addressed today. Poultry manure is discarded outside the poultry farms, where it is either filled with pits not suitable for storage or unloaded in a specially designated area. Afterwards, it is not used and causes tremendous damage to the environment. At the same time, bird droppings contain high macro and microelements, which form the basis for their value as organic fertilizers. The article analyzes and summarizes the practical use of biotechnological processing of bird droppings into a fertilizer and its further application on strawberry seeds as one of the reasonable solutions to the economic and environmental safety of poultry production under industrial conditions. The relevance of the topic. The solution to the problem of manure recycling is to improve the environmental situation, soil fertility and crop yields. The research is aimed at processing organic poultry waste and the impact of organic fertilizer, which is based on chicken manure, on soil fertility and crop yields. The laboratory and field studies on poultry waste management have been carried out on the territory of OOO Silver Eagle Plus (LLC) poultry farm in Tashkent region using the method of anaerobic fermentation and assessment of organic fertilizer quality as the most rational one for agriculture. The studied objects have been organic waste from OOO Silver Eagle Plus (LLC) poultry farm in Tashkent region, meadow soil and Joydori strawberry seeds. The research results have shown that the method of methane digestion is effective against pathogens in organic poultry waste; the process increases the number of useful bacteria and the generation of metabolites such as organic acid. Biotechnological poultry waste disposal reduces the processing time of the source material by 1.5 times. The study has revealed that the application of organic fertilizer based on chicken droppings has had a positive impact on soil structure, which has enhanced its aeration and ensured proper vegetative root system development.